Mongolia : Towards a High Performing Civil Service - World Bank (Washington, DC, 2014)
The objective of this report is to identify specific steps that the Government of Mongolia can take over the next three years to improve the performance of the civil service. Civil service reform impacts both the investment climate and the development of a robust private sector, and sustained improvements in service delivery. This report aims to capitalize on this window of opportunity and provide advice on what should be the key strategic reform priorities for the Government. The report identifies three key areas of reform for the Government. First, the civil service grading and compensation system requires significant changes in order to be able to attract and retain high caliber staff. Second, Mongolia needs to move in a phased manner towards centralized payroll administration in order to enhance establishment and expenditure controls. Third, the personnel management regime needs to be improved as it presently does not fully protect civil servants from undue political interference, there is a lack of clarity over the precise recruitment modalities for the senior administrative civil service positions, and limited horizontal mobility that negatively impacts career development. The report specifies a number of immediate steps that can be taken to resolve these issues.